Pendugaan Karbon Tersimpan di Berbagai Jalur Hijau Jalan Arteri Sekunder Kota Medan Bagian Tengah (Estimation of Carbon Stored in Different Green Line Arterial Road Secondary Central Part of Medan City) - Elisa Manik; Siti Latifah; Pindi Patana (Peronema Forestry Science Journal, 2016)
Green belt is one of the green open spaces are quite effective in absorbing carbon emissions and pollutant gases around the highway in the city.  Plants were grown in a green belt has the ability to absorb carbon emissions. Because it is necessary to do the calculation of the carbon stored in various green belt in the secondary arterial roads Medan city. The purpose of this research was to calculate the potential carbon is stored in various green belt in the secondary arterial roads Medan. Sampling lines and plant samples was conducted using purposive sampling and census methods. Calculation data using allometric models. The results showed that there are 8 types of plants on the green belt of research of the kind that most dominating is Palem Raja (Oreodoxa regia). The highest value of carbon stored by type of plant found in plant angsana (Pterocarpus indicus) with a total value of carbon stored in the 8 green belt, namely 525,337 Ton/Ha, or an average of 65,67 Ton/Ha. The highest value of carbon stored by the green belt of research there is on the path to Balai Kota street, district of Medan Barat with a value of 274,985 Ton/Ha. Keywords: green belt, carbon stock, secondary arterial roads, allometric models.